A survey on primary school teacher's job satisfaction in the Lundu district, Sarawak - Dzulkiflee, Abdullah (2003)
Job satisfaction is one of the most important and well-researched attitudes in organizations behavior. This survey aims to extend the research on the sources affecting job satisfaction and level of job satisfaction among teachers in primary schools in the Lundu District.